Exploring the Philosophy and Forms of Traditional Balinese Architecture at Badung Market - I Kadek Pranajaya; I Nyoman Artayasa (Journal of Urban Society's Arts, 2022)
After the fire disaster, Badung market was rebuilt by applying the values of Balinese  local wisdom. It was designed through an integrated synergy of regional arrangement within the Badung market, Kumbasari market, and the arrangement of the Tukad Badung to support the concept of a heritage city tour in Denpasar City. The philosophical concept used is tapak dara and padu raksa. The concept of values and architectural forms uses the Triangga, the Trimandala, the Sanga Mandala, and the Tri Hita Karana concepts. The forms of the entrance uses the bintang aring concept. It is combined with the kayon form as a symbol of balance, horizontal and vertical for human life. The concept of Balinese traditional architectural decoration uses bebadungan decorations. This research was with a qualitative exploratory method Researchers also found modernization towards more advanced changes with rational, effective, efficient, and economic principles. This is evidenced in the use ornaments made of Glass Reinforced Concrete, elevator facilities, and escalators. In addition, Badung market was designed to be more modern and universal with a children's play room, lactation room, emergency stairs, accessible toilets, and other facilities.Menjelajahi Filosofi dan Bentuk Arsitektur Tradisional Bali di Pasar Badung.  Pascabencana kebakaran, Pasar Badung dibangun dengan menerapkan nilai kearifan lokal Bali. Didesain melalui sinergitas penataan kawasan secara terpadu antara Pasar Badung, Pasar Kumbasari, dan penataan tukad Badung untuk menunjang konsep tur kota pusaka (heritage city tour) Kota Denpasar. Konsep filosofis yang digunakan adalah tapak dara sebagai simbol keseimbangan dan padu raksa sebagai makna stabilitas perputaran ekonomi masyarakat untuk peningkatan kesejahteraan. Konsep tata nilai dan bentuk bangunan menggunakan konsep triangga, trimandala, sanga mandala, dan tri hita karana. Bentuk pintu masuk pada bangunan utama menggunakan konsep bintang aring dengan bebatelan di kiri dan kanan. Bintang aring difilosofikan sebagai pintu yang bercahaya bagai bintang sehingga terlihat monumental, berestetika, dan menambah kesan oriental. Bintang aring dikombinasikan dengan bentuk kayon sebagai lambang keseimbangan, horisontal dan vertikal bagi kehidupan manusia. Konsep ragam hias arsitektur tradisional Bali menggunakan ragam hias bebadungan. Ragam hias ini didesain untuk menciptakan identitas jati diri Kota Denpasar. Peneliti juga menemukan kehidupan modernisasi dengan prinsip rasional, efektif, efisien, dan ekonomis. Hal ini dibuktikan pada penggunaan ornamen dari bahan Glass Reinforced Concrete (GRC), fasilitas elevator, dan eskalator. Selain itu Pasar Badung didesain lebih modern dan universal dengan adanya ruang bermain anak, ruang laktasi, tangga darurat, toilet aksesibel, dan fasilitas lainnya.